O SISTEMA ÚNICO DE ASSISTÊNCIA SOCIAL: desafios à sua implementação - Arlete de Brito Abreu (Universidade Federal do Maranhão, 2014)
This article approaches the National Social Assistance Policy from SUAS - design and structuring. The national debate about the Social Assistance through SUAS and its affirmation as a right of citizenship. Challenges in the implementation process of SUAS: decentralization, co-financing; work; ongoing and continuing training of workers. The SUAS in São Luis - MA: demands and challenges.